(untitled) (International Journal of Scientific Trends, 2025)
Basketball is a team sport in which teamwork, strategic thinking, and leadership play a major role. Individual skills are not enough to create an effective team, but also the understanding of each other, adaptation to tactics, and leadership skills of players. This article analyzes the basic principles of team play, types of leadership, and their impact on team results. It also examines the role of coaches and leading players in motivating the team. Strategies for creating an effective team are highlighted based on modern research and practical experience. The importance of factors such as communication, mutual trust, and quick adaptation to the situation in order to increase efficiency in the process of team play is emphasized. This study serves as a guide for coaches, players, and sports experts.